Gentiles in Matthew’s infancy narrative - Lee, K; Viljoen, FP (Nederduitse Gereformeerde Teologiese Tydskrif, 2010)
Scholars have frequently argued that the great commission rather than the beginning should be regarded as the key to the understanding of Matthew’s narrative. Yet, the beginning of the gospel has several themes and elements that match with those of the ending. In some sense, the infancy narrative may be designated as a thematic prelude of the Gospel, similar to the exordium in classical rhetorical speeches. Therefore, the beginning and the ending usually match each other, even though the clues in the beginning are tiny, sometimes even unnoticeable by itself. The themes grow big to be noticeable and become more apparent as the story unfolds, until they are fully grown in the great commission at the end.